Association Between ABO Blood Groups and Cancer Susceptibility in the Libyan Population - Salah Elbaruni; Nidal Bilkhier; Gomaa Sulaiman (Khalij-Libya Journal of Dental and Medical Research, 2025)
While earlier studies have demonstrated the impact of blood groups on numerous diseases, such as cardiovascular disease and infections, researchers have also revealed intriguing links between certain blood groups and the risk of certain cancers. Evidence suggests that individuals with blood type O have a slight decrease in risk for certain digestive cancers. Whereas individuals who carry blood types A, B, and AB seem to have greater susceptibility to various types, including pancreatic, lung, breast, colorectal, and cervical cancers. However, the exact causes remain unclear, there is growing speculation that some genetic factors within the ABO region may affect the processes of angiogenesis and immune system responses. Bridging these gaps stands to transform strategy for personalized cancer therapies. The purpose of this study, therefore, is to determine the relationship between ABO blood group types and the prevalence of cancer. In analyzing these relationships, the study aims to advance efforts toward more targeted strategies for the prevention and treatment of cancer. We harvested information from the cancer registry of a university hospital affiliated with a tumor registry on 300 Libyan patients aged between 25-85 years, categorized them into eight different types of cancers. Our data collection was through three processes: first, analysing the blood of the cancer patients, second, reviewing the medical files of the patients, and last, distributing public questionnaires. This study has represented differences in the types of cancer that patients may have based on their blood type. Due to the multifaceted approach to data collection, the insights provided from the study can significantly improve the impact of treatment interventions for the advancement of cancer research. During the study, the most prevalent blood group was O+, followed closely by A+. O+ blood type predominated in patients suffering from colon and pancreatic malignancies, while A+ was more frequent in those with lung and prostatic cancers. Fewer cancer patients were found to have an AB blood group. Other relationships regarding blood types and malignancy will be analysed statistically and graphically. Interpreting and understanding blood groups may facilitate the development of personalized healthcare strategies, particularly for high-risk individuals, allowing for targeted interventions to improve overall well-being. Further research, including functional studies, genetic studies and immunological mechanisms, remains necessary to elucidate the impact of ABO antigens on tumor development and prevention.